Phosphate sorption of some Nigerian soils and its effect on cation exchange capacity - Juo, A.S.R.; Maduakor, H.O. (Informa UK Limited, 1974)
Langmulr phosphate sorption isotherms for several representative Nigerian soils derived from different parent materials were studied. Two straight‐line portions of the isotherm were obtained for each soil studied after 24‐hour equilibration. The number of straight‐line portions or “breaks”; of the isotherm for a soil was found to depend not only on the P concentration range but on the time of equilibration as well.Phosphate sorption capacity of the soil studied follows the order: Alfisols from basalts > Ultisols from sandstone > Alfisols from basement complex rocks (gneisses) ˜ Alfisols from coastal sediments ˜ Alfisols from eolian drift. The sandy forest soils derived from basement complex rocks and from coastal sediments in south‐western Nigeria require relatively low amounts of phosphate for maximum crop yield as determined by the Langmuir isotherm.Phosphate sorption resulted in significant increases in cation exchange capacity of the soils studied. The percentage CEC increase ranged from 17% to 370%.